SIKAP SISWA TERHADAP SAINS DALAM PEMBELAJARAN FISIKA DENGAN PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 5E BERBANTUAN PETA KONSEP PESERTA DIDIK KELAS XI SMAIT AL-FITYAH PEKANBARU - Abdul Khair; Zuhdi Ma’ruf; Azhar Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study was to describe students' attitudes toward the science of students of class XI Alfath SMA IT Al-Fityah Pekanbaru with the implementation of learning cycle 5e model assisted concept maps on dynamic fluid materials. The research form was Pre-Experimental Design (pre-test and post-test group. The subject of this study was 20 students of class XI Alfath. A questionnaire of students' attitudes toward the science was given to the students before and after learning as the instrument in collecting the data. Data were analysed using descriptive analysis. The result of the research showed that the students 'attitude toward science was in the high category before (pre-test) and after learning (post-test). In line with that, the students' attitude toward the science was also increased by the implementation of 5e learning cycle concept map model. Thus, it can be concluded that the implementation of 5e learning cycle assisted concept map model can improve students' attitudes toward science in Physics learning on dynamic fluid material in SMA IT Al-Fityah Pekanbaru.Keywords: Learning Cycle 5e Assisted Concept Maps Model, Student’s Attitudes toScience.